Hybrid Solid State-Submerged Fermentation Using a Matrix (2019)
The subject invention provides methods and systems for producing microbe-based compositions that can be used in the oil and gas industry, environmental cleanup, agriculture, and many other applications. More specifically, the subject invention provides methods and systems for producing microorganisms and/or growth by-products thereof using a hybrid solid state-submerged fermentation method, wherein a matrix comprised of a solid material covered in an alginate coating is formed inside a liquid fermentation vessel. In some embodiments, the solid material is a plurality of natural loofa sponges.